2003
DOI: 10.1029/2003jb002428
|View full text |Cite
|
Sign up to set email alerts
|

Study on finite strain and its relationship with magnetic fabric along Ailao Shan‐Red River shear zone

Abstract: [1] The finite strain along Ailao Shan-Red River shear zone has been studied. The axial ratios of strain markers and shear strains vary greatly, arising principally from deformation intensity and from contrasting competencies. Ellipticity of chloritic amygdales in basalt ranges from 6.79 to 10.47 (corresponding shear strain g xz = 2.22-2.93), and ellipticity of garnets from 1.56 to 2.95 (g xz = 0.45-1.14) in core gneiss. The S-C angle of the sheared rocks varies from 2°to 28°(g sc = 1.35-28.60), mostly in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…4). Zhou et al (2003) observed that amplification effects due to thick sediment are frequency-dependent for periods less than about 8 s, and that these cannot be modelled by a frequency-independent station amplitude correction term. We suspect therefore that this dispersion is at least partially due to surface sediment effects.…”
Section: Frequency Dependence Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…4). Zhou et al (2003) observed that amplification effects due to thick sediment are frequency-dependent for periods less than about 8 s, and that these cannot be modelled by a frequency-independent station amplitude correction term. We suspect therefore that this dispersion is at least partially due to surface sediment effects.…”
Section: Frequency Dependence Of the Datamentioning
confidence: 99%
“…We suspect therefore that this dispersion is at least partially due to surface sediment effects. Zhou et al (2003) observed that amplification effects due to thick sediment are frequency-dependent for periods less than about 8 s, and that these cannot be modelled by a frequency-independent station amplitude correction term. With increasing frequency, amplitude anomalies increase in magnitude and become more scattered.…”
Section: Frequency Dependence Of the Datamentioning
confidence: 99%